Modern vs Traditional: Comparative Study of Efficacious Arabic Language Learning Methods - Pratama, Budi; Kadar, Haerani; Husaini, Busyro; Aziz, Muslih Abdul; Saputra, Dimas Adi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
Ineffective use of learning methods in the conditions and circumstances of students caused the obtained learning objective not achieved or below the standard. This case was determined to be the background for this research. This article described and analyzed the comparative of efficacious methods, modern and traditional learning methods, in Arabic learning. This type of research was an experimental research with a descriptive quantitative approach. The population of this study were fourth-grade students in class IV-A, IV-B and IV-C at MI Al-Ma'had An-Nur Bantul Yogyakarta. Meanwhile, the sample for this research was class IV-A and IV-B with each class consisting of 21 students. The sample in this research was selected with purposive sampling technique. Data collection were obtained through tests, observations, interviews and documentation. Hypothesis testing in this study used a paired sample t-test calculated using the SPSS version 25 application. The results of this study showed that there was a difference in success between modern learning methods of 84.05 and traditional learning methods of 64.05 in accordance with the results of the paired sample test (t-test). Hence, it can be concluded that the results after modern learning methods implementation are considered more effective to apply in the Arabic language learning process. It was expected that the results of this research could be a reference for teachers in determining suitable learning methods for students in the teaching and learning process.